Interactive effects of age and multi-gene profile on motor learning and sensorimotor adaptation. (April 2016) - Noohi, Fatemeh; Boyden, Nate B.; Kwak, Youngbin; Humfleet, Jennifer; Müller, Martijn L.T.M.; Bohnen, Nicolaas I.; Seidler, Rachael D.
Abstract: The interactive association of age and dopaminergic polymorphisms on cognitive function has been studied extensively. However, there is limited research on whether age interacts with the association between genetic polymorphisms and motor learning. We examined a group of young and older adults' performance in three motor tasks: explicit sequence learning, visuomotor adaptation, and grooved pegboard. We assessed whether individuals' motor learning and performance were associated with their age and genotypes. We selected three genetic polymorphisms: Catechol-O-Methyl Transferase (COMT val158met) and Dopamine D2 Receptor (DRD2 G>T), which are involved with dopaminergic regulation, and Brain Derived Neurotrophic Factor (BDNF val66met) that modulates neuroplasticity and has been shown to interact with dopaminergic genes. Although the underlying mechanisms of the function of these three genotypes are different, the high performance alleles of each have been linked to better learning and performance. We created a composite polygene score based on the Number of High Performance Alleles (NHPA) that each individual carried. We found several associations between genetic profile, motor performance, and sensorimotor adaptation. More importantly, we found that this association varies with age, task type, and engagement of implicit versus explicit learning processes. Highlights: We tested the association of COMT, DRD2, and BDNF polymorphisms with motor learning. We found that these snps were associated with motor performance and sensorimotor adaptation. This association varied with age and engagement of implicit versus explicit mechanisms.